TOPOLOGICAL INDICES IN HYPERTUBES OF HYPERCUBES - FATHALIKHANI, Khadijeh; PÎRVAN-MOLDOVAN, Atena; DIUDEA, Mircea V. (Studia Universitatis Babeș-Bolyai Chemia, 2016)
A topological index is a single number descriptor that characterizes the molecular graph topology up to isomorphism. Hyper-tubes, open or closed, consisting of hyper-cubes of n-dimensions have been designed and formulas for some topological indices, counting vary substructures or characteristics, were established.